Reconstructing the Father’s Educational Role in the Qur’anic Perspective: Insights from the Tafsir of Surah Luqman Verses 12–19 - Krisna Yuda; Pranoto, Muhammad Solihin (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
Children have an important role in household life, where the position of children is not only as a complement but a gift given by Allah SWT to parents, so that parents have an obligation to educate children based on the Qur'an. This study aims to examine the role of fathers in children's education based on the provisions of Surah Luqman verses 12-19 with the Ibn Katsir interpretation approach. In these verses, Allah SWT presents the figure of Luqman as a wise and responsible father figure to teach his children faith, worship, and morals. The results of the study show that the father is the main teacher who shapes the character and faith of children. To produce a generation that is faithful and has noble morals, education that is given with full wisdom, gentleness, and example is very important. This study confirms that the active involvement of a father in the process of educating a child is very important, as indicated by Luqman al-Hakim.